O debate presidencial de 2021 entre Marcelo Rebelo de Sousa e André Ventura: estratégias de argumentação e de persuasão - Braz, Ana; Marques, Isabelle Simões (Revista da Associação Portuguesa de Linguística, 2022)
We are looking at a linguistic-discursive analysis of the most recurrent strategies of argumentation and persuasion in the TV debate of January 6, 2021 for the 2021 presidential elections in Portugal. In this debate, two candidates are opposed, namely Marcelo Rebelo de Sousa - President of the Republic at the time, and in the meantime elected for a second term - and André Ventura, deputy of the Assembly of the Republic and candidate for the Chega party. Our analysis focuses on the manipulation strategies used by both speakers and candidates. The images that the political opponents build of themselves and of their opponent in and by discourse, the emotions that their words arouse, the predominant discursive topic, the main axiological values of the lexemes and expressions used, and the ways of refuting facts and views conveyed in the different verbal exchanges are studied. The present work is part of the perspective of discourse analysis (Kerbrat-Orechioni, 2005 and 2014), as well as within the framework of the study of argumentation, namely argumentation in the political discourse, in the path of Amossy (2000) and Plantin (1996), considering the contributions of Charaudeau (2005, 2008 and 2016) on the political discourse and Marques on the Portuguese political discourse (2009, 2013 and 2017).